10)
Ta có x^2 + x + y + y^2 = 8 và x + xy + y = 5
<=> x^2 + x + y + y^2 = 8 và 2(x + xy + y) = 10
<=> (x^2 + x + y + y^2) + 2(x + xy + y) = 18 và 2(x + xy + y) = 10
<=> (x + y)^2 + 3(x + y) = 18 và 2(x + xy + y) = 10
<=> (x + y + 1,5)^2 = 20,25 và 2(x + xy + y) = 10
<=> x + y + 1,5 = 4,5 hoặc x + y + 1,5 = -4,5 và 2(x + xy + y) = 10
<=> x + y = 3 hoặc x + y = -6 và 2(x + xy + y) = 10
TH1 x + y = 3 và x + xy + y = 5
<=> x + y = 3 và xy = 2
<=> x = 3 - y và xy = 2
<=> x = 3 - y và (3 - y)y = 2
<=> x = 3 - y và 3y - y^2 = 2
<=> x = 3 - y và y^2 - 3y + 2 = 0
<=> x = 3 - y và (y - 1)(y - 2) = 0
<=> x = 3 - y và y = 1 hoặc y = 2
<=> (x ; y) là (2 ; 1) ; (1 ; 2)
TH2 x + y = -6 và x + xy + y = 5
<=> x + y = -6 và xy = 11
<=> x = -6 - y và xy = 11
<=> x = -6 - y và (-6 - y)y = 11
<=> x = -6 - y và -6y - y^2 = 11
<=> x = -6 - y và y^2 + 6y + 11 = 0
<=> x = -6 - y và (y + 3)^2 + 2 = 0 (vô lí)
Vậy (x ; y) là (2 ; 1) ; (1 ; 2)